Cover Image, Volume 62, Issue 2. Issue 2 (19th January 2023) - Pimentel, Julio M.; Zhou, Jun‐Ying; Wu, Gen Sheng
Abstract : The cover image is based on the Research Article Regulation of programmed death ligand 1 (PD‐L1) expression by TNF‐related apoptosis‐inducing ligand (TRAIL) in triple‐negative breast cancer cells by Julio M. Pimentel et al., https://doi.org/10.1002/mc.23471 .